Experimental Study to The Effect of Applying Stressing Force on Etched Polarization Maintaining Fiber as Hybrid Fabry-Perot /Mach-Zehnder inline fiber interferometer - Noori, Nada Faris; Mansoor, Tahreer Safaa (Iraqi Journal of Laser, 2021)
Abstract: The increased interest in developing new photonic devices that can support high data rates, high sensitivity and fast processing capabilities for all optical communications, motivates a pre stage pulse compressor research. The pre-stage research was based on cascading single mode fiber and polarization maintaining fiber to get pulse compression with compression factor of 1.105. The demand for obtaining more précised photonic devices; this work experimentally studied the behavior of Polarization maintaining fiber PMF that is sandwiched between two cascaded singe mode fiber SMF and fiber Bragg gratings FBG. Therefore; the introduced interferometer performed hybrid interference of both Mach-Zehnder and Fabry-Perot interferometers. The hybrid interference is resulted from the interference of the forward, backward and X,Y polarization components of the propagating light along the cascaded fibers. In conclusion spectral pulse compression with maximum compression factor in range of 3-6 was obtained by tuning applied stress on the shortest etched PMF segment of the interferometer (i.e. 8cm length). Such interferometer can support fine tunable all optical band pass filter